(untitled) (Marketing Journal, 2024)
This paper examines the pivotal role of electronic document circulation in enhancing operational efficiency and promoting sustainable practices within organizations, particularly in the context of Bukhara’s burgeoning green economy. With a focus on reducing paper consumption, minimizing carbon footprint, and streamlining workflows, the adoption of electronic document management systems (EDMS) presents a compelling avenue for businesses to embrace sustainability while optimizing their processes. Drawing upon case studies and empirical research, this paper elucidates the multifaceted benefits of transitioning from traditional paper-based documentation to electronic platforms. Furthermore, it explores the challenges and opportunities associated with implementing EDMS in the unique socio-economic landscape of Bukhara. By facilitating seamless information exchange, improving accessibility, and fostering collaboration, electronic document circulation not only drives efficiency but also aligns with the broader objectives of environmental conservation and sustainable development. This paper offers insights, strategies, and best practices for organizations seeking to leverage digital technologies to propel their transition towards a greener, more resilient future in Bukhara’s evolving economic ecosystem.